Penanaman Sengon dalam Gerakan Penghijauan di Desa Sukoharjo, Kecamatan Tirtomoyo, Kabupaten Wonogiri - Hery Widijanto; Suwarto Suwarto (Universitas Sebelas Maret, 2019)
Title: Planting Sengon by Afforestation in Sukoharjo Village, Tirtomoyo District, Wonogiri Regency. This service activities aimed at introduce the vegetative conservation methods for minimized erosion and conserve land resources by afforestation with sengon. This activity was in collaboration with two partners, namely: (1)